"Seek, test, treat and retain" for hepatitis C in the United States criminal justice system. Issue 3 (19th August 2014) - Larney, Sarah; Beckwith, Curt G; Zaller, Nickolas D; Montague, Brian T; Rich, Josiah
Abstract : Purpose: To consider the potential benefits and challenges of applying a strategy of 'seek, test, treat and retain' (STTR) to hepatitis C virus (HCV) in the United States (US) criminal justice system. Design/methodology/approach: We draw on the published literature to illustrate how each component of STTR could be applied to HCV in the US criminal justice system, and describe challenges to the implementation of this strategy. Findings: The burden of morbidity and mortality associated with chronic hepatitis C virus (HCV) infection in the United States is increasing and without significantly increased treatment uptake, will likely continue to do so for several decades. We argue that the US criminal justice system is an ideal focus for HCV case-finding and treatment due to a high prevalence of infection and large volume of individuals in contact with this system. STTR would identify large numbers of HCV infections, leading to opportunities for secondary prevention and primary care. Important challenges to the implementation of STTR include treatment costs and training of prison medical providers. Originality/value: This paper highlights opportunities to address HCV in the US criminal justice system.